Efektivitas Ekstrak Etanol Daun Jeruk Purut (Citrus hystrix DC) Sebagai Larvasida Nyamuk Aedes aegypti - Esy Maryanti; R. Della Marta; M Yulis Hamidy (Fakultas Kedokteran Universitas Riau, 2011)
Dengue Hemorrhagic Fever is caused by dengue virus and spread by Aedes aegypti as primarily vector. Preventingdengue virus transmission depends on control of the mosquito vectors. Kiffer lime is one of the potential plants as abotanical larvacidal. The aim of this study was to investigate kiffer lime larvacidal ability against Ae.aegypti larvaebased on LC50 and LC90 levels by probit analize. The design of this research was experimental including preliminarytest and final test. 525 samples of Ae.aegypti larvae instar III/IV were used in this study and divided in to six groupsof experiment. The result were from observation of the larvae mortalities within 24 hours. Assassement of larvacidalefficacy demonstrated that kiffer lime leaf were toxic against Ae.aegypti larvae. LC50 value is 4015,880 ppm and LC90value is 6961,822 ppm. Ethanol extract of kiffer lime leaf could be considered as a potentially alternative source forbotanical larvacides.